2013
DOI: 10.1074/jbc.m112.419101
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting Protein Mediates High Glucose-induced Reactive Oxygen Species Generation by Mitochondria and the NADPH Oxidase, Nox4, in Mesangial Cells

Abstract: Background: Thioredoxin-interacting protein (TxNIP) is up-regulated by high glucose (HG), inhibits the antioxidant, thioredoxin, and thereby is implicated in oxidative stress. Results: TxNIP deficiency protects mesangial cells from HG-induced oxidative stress and increased collagen by blocking mitochondrial glucose metabolism, NADPH oxidase, and Nox4. Conclusion: TxNIP controls ROS generation by regulating the TCA cycle versus glycolytic glucose flux. Significance: Inhibition of TxNIP is a promising approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 76 publications
13
112
0
Order By: Relevance
“…Down-regulation of cellular and mitochondrial Nox4 with siRNA prevents Ang II-induced increase in mitochondrial superoxide production, identifying Nox4 as a prominent source of mitochondrial ROS in MCs treated with Ang II. These data are in agreement with the recent findings showing that high glucose and Ang II enhance mitochondrial Nox4 expression and the subsequent increase in ROS generation in renal cells (21)(22)(23).…”
Section: Discussionsupporting
confidence: 93%
“…Down-regulation of cellular and mitochondrial Nox4 with siRNA prevents Ang II-induced increase in mitochondrial superoxide production, identifying Nox4 as a prominent source of mitochondrial ROS in MCs treated with Ang II. These data are in agreement with the recent findings showing that high glucose and Ang II enhance mitochondrial Nox4 expression and the subsequent increase in ROS generation in renal cells (21)(22)(23).…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, our experiments with THP1 cells cultured under various HG/NG conditions revealed an association between persistent DNA-me triggered by prior history of HG exposure and enhanced TXNIP expression in response to HG in vitro. We, thus, speculate that transient hyperglycemic episodes during the EDIC Study would induce more TXNIP overexpression and cellular dysfunction in cases vs. controls because of TXNIP hypo-me, which is in line with the reported adverse cellular roles of TXNIP (43)(44)(45)48). This type of cellular response to episodic HG provides mechanistic information toward understanding the connections between persistent DNA hypo-me at TXNIP and its gene expression and hence, metabolic memory of diabetic complications.…”
Section: Discussionsupporting
confidence: 66%
“…Persistence of DNA hypo-me in TXNIP at two time periods was particularly interesting, because TXNIP is a reported sensor of glucose stress, a prooxidant, and a proapoptotic protein, with gene expression that is highly associated with hyperglycemia and diabetic complications, including retinopathy and nephropathy (43)(44)(45), both of which were prevalent in our case group. TXNIP expression is highly induced by HG in various cell types (46)(47)(48), which by inhibiting thioredoxin, subsequently causes oxidative stress and apoptosis.…”
Section: Resultsmentioning
confidence: 90%
“…14 In addition, we recently reported that TxNIP enhances HG-induced mitochondria-derived O 2 2 (superoxide) as well as cellular ROS, at least in part, by augmenting the mitochondrial and cytosolic NADPH oxidase isoform, Nox4, in cultured mesangial cells. 15 Thus, by increasing the generation and decreasing the degradation of ROS, HG-induced TxNIP may contribute to glucotoxicity, as observed by others and our group in pancreatic b cells. 13,16,17 To elucidate the role of TxNIP in the pathogenesis of DN in vivo, we explored the action of TxNIP in the diabetic kidney of wild-type (WT) and TxNIP 2/2 (knockout [KO]) mice.…”
supporting
confidence: 60%
“…15 BPs were lower in both diabetic groups, likely reflecting a degree of volume contraction due to fluid loss ( Table 2).…”
Section: Txnip Deficiency Prevents Albuminuria In Stz-induced Diabetementioning
confidence: 99%